Deep vein thrombosis after open hepatectomy or other major upper abdominal surgery in Taiwan - Hsuan-Yu Lin; Yao-Li Chen; Ching-Yeh Lin; Han-Ni Hsieh; Ya-Wun Yang; Ming-Ching Shen (Journal of the Formosan Medical Association, 2023)
Backgroud/purpose: Venous thromboembolism, including deep vein thrombosis (DVT) and pulmonary embolism (PE), is an important complication in patients who underwent open hepatic surgery as well as other major upper abdominal surgery. This study aims to investigate the occurrence of postoperative DVT without pharmacological thromboprophylaxis in such cohorts in Taiwan. Methods: This is a prospective, cross-sectional cohort study conducted from March 2010 to December 2011. Patients who underwent major upper abdominal surgery, including open hepatectomy, were enrolled. Color duplex compression ultrasonography (CUS) was used to detect DVT. Symptomatic PE was excluded if there were no suggestive respiratory symptoms or sudden death. Relevant clinicopathological and surgical information of each patient was collected and analyzed. Results: 195 patients (118 male and 77 female) were enrolled, with a median age of 63.6 years. The majority (169/195, 88.7%) were treated for active malignancy. Totally 147 patients received open hepatectomy. Only one asymptomatic and distal postoperative DVT event was identified by CUS, which occurred on a 73-year-old female patient who received a left lateral segmental hepatectomy for removing the advanced hepatocellular carcinoma (pathologic stage, T3aN0M0). No cases of symptomatic PE or sudden death were observed. No correlation between DVT and precipitating factor was demonstrated in our cohort. Conclusion: Without pharmacological thromboprophylaxis, a low rate of postoperative DVT among patients undergoing open hepatectomy (0.7%, 1/147) or major upper abdominal surgery (0.5%, 1/195) in Taiwan was reported. A distinctively regional role of pharmacological thromboprophylaxis for hepatic surgery was also suggested by our data.